P249 Physicians' opinion: ceilings of therapy in chronic obstructive pulmonary disease (PILOT study). (16th November 2010) - Gallagher, J L; Morton, B; Clegg, I; Walker, J; Davies, L
Abstract : Introduction: Acute exacerbations of chronic obstructive pulmonary disease (COPD) are a common reason for hospital admission. Treatment depends upon the severity of presentation and background physiological status. The COPD NICE guidelines (2010) state that when patients are started on NIV, there should be a clear plan covering what to do in the event of deterioration and ceilings of therapy should be agreed.1 We sought to explore decision making among clinicians with responsibility for interventional treatments in difficult scenarios. Method: We questioned intensive care and respiratory clinicians in two deaneries. We described six hypothetical patients with COPD who presented to an A&E department in hypercapnic respiratory failure. The histories given were of end stage COPD, ischaemic heart disease, complicated diabetes mellitus, advanced age, potentially curable bronchial carcinoma and non-concordance with treatment. Results: One hundred and thirteen questionnaires were collected; 58 intensive care medicine (ICM) clinicians (28 consultant and 30 specialist trainees) and 55 respiratory medicine physicians (13 consultant and 42 specialist trainees). The majority of respondents would intervene in the presented scenarios, either with invasive or non-invasive ventilation as illustrated in graph 1. No statistical difference in decision making was demonstrated between ICM and respiratory clinicians. Statistical kappa analysis (Intercooled Stata 9.0) demonstrated 'fair' agreement among ICM trainees, respiratory trainees and consultants when choosing non-invasive (0.32, 0.41, 0.33) and invasive ventilation (0.29, 0.39, 0.36) with 'slight' agreement among ICM consultants (non-invasive 0.12 and invasive ventilation 0.22). Some respiratory physicians felt that they required additional information, such as results of spirometry, to make informed decisions. However, in an acute setting, such information is often unavailable so was not included in the vignettes. The opportunistic nature of data collection meant that a response rate could not be calculated. Conclusion: This pilot study did not demonstrate a difference in decision making between respiratory and intensive care specialities. With development of the vignettes this methodology could form the basis for a national survey on ceilings of therapy in COPD to inform the individual clinician when making difficult decisions.